UJI KETAHANAN BEBERAPA GENOTIPE TANAMAN KARET TERHADAP PENYAKIT Corynespora cassiicola DAN Colletotrichum gloeosporioides DI KEBUN ENTRES SEI PUTIH - Intan Purnamasari; Lahmuddin Lubis; Maryani Cyccu Tobing; Zaidah Fairuzah (Universitas Sumatera Utara, 2014)
Research on title resistence test of rubber plant genotype by Corynespora cassiicola andColletotrichum gloeosporioides diseases at Sungei Putih budstock rubber plantation. This researchwas to study to determine resistence of rubber plant genotype against C. cassiicola andC. gloeosporioides at budstock rubber plantation. This research had been conducted atexperimental field of Sungei Putih Rubber Research Center in May-July 2013 using split plotdesign with two factor, i.e genotype plants (930, 135, 38, 51, 65, 100, 108, 118, 222, 223, 227, and374) and diseases type (no disease, C. cassiicola and C. gloeosporioides). The results showed thatthe fastest incubation periode (3 days) contained on genotype 223 and 930, the slowest (6 days) ongenotype 222. The lowest disease severity (20,99%) of C. cassiicola treatment contained ongenotype 100 and the highest (33,33%) was at genotype 65. The lowest disease severity (21,61%)of C. gloeosporioides treatment contained on genotype 222 and the highest (57,41%) was ongenotype 223. The highest total spot (58,56 spots) contained on combination treatment of genotype223 with C. gloeosporioides disease and the lowest (1,70 spots) on combination treatment ofgenotype 100 with C. cassiicola disease.Key Words: Genotype plant rubber, Corynespora cassiicola, Colletotrichum gloeosporioides